Impact of Hands-on Activities on Students’ Performance in Biology in Ghanaian Senior High Schools: A Systematic Analysis - Richmond Mensah; Isaac Kwame Boafo; Thomas Dawuni Tingbanja (Journal of Research in Education and Pedagogy, 2026)
This study investigates the impact of hands-on activities on students’ academic performance, motivation, and attitudes toward biology in Ghanaian senior high schools through a systematic analysis of existing literature. Grounded in constructivist and experiential learning theories, the study synthesizes evidence on how practical, activity-based instruction enhances students’ understanding and retention of biological concepts by linking theory to real-life applications. A systematic literature review was conducted in accordance with PRISMA guidelines, drawing on 32 peer-reviewed articles, unpublished theses, and policy documents published between 2010 and 2025. Data were sourced from Google Scholar, ResearchGate, Academia.edu, and official Ghana Education Service and Ministry of Education repositories. The findings consistently indicate that the integration of hands-on activities significantly improves students’ conceptual understanding, long-term retention, critical thinking skills, and overall academic performance in biology. Additionally, practical activities were found to positively influence students’ motivation, engagement, and attitudes toward learning biology by creating interactive and student-centered learning environments. Despite these benefits, the review identifies persistent challenges to effective implementation, including inadequate laboratory resources, large class sizes, limited instructional time, and insufficient teacher training. These constraints are particularly pronounced in under-resourced schools, limiting equitable access to experiential learning opportunities. The study concludes that strengthening hands-on biology instruction through improved resource provision, targeted teacher professional development, and curriculum adjustments is essential for enhancing learning outcomes. The findings provide valuable insights for educators, curriculum developers, and policymakers seeking to improve biology education and promote meaningful science learning in Ghanaian senior high schools.